A depth-first search algorithm for oligonucleotide design in gene assembly - Liang, Hanjie; Chen, Zengrui; Fang, Gang (Frontiers in Genetics, 2022)
When synthesizing gene with long DNA sequence, it is usually necessary to divide the whole sequence into several fragments. Based on these fragments, oligonucleotides set for gene assembly is produced. Each oligonucleotide is synthesized separately by chemical means, then the obtained oligonucleotides are assembled into long sequence gene in a specific environment with polymerase chain reaction (PCR) or ligase chain reaction (LCR). In this paper an effective and efficient algorithm to divide long genes into oligonucleotide sets is presented. Firstly, according to the length of oligonucleotide overlapped region, the long DNA sequence to be synthesized is divided into fragments with approximate equal length. Secondly, the length of these fragments is iterated to dynamically optimize the length of overlapped region to lower the melting temperature fluctuation of oligonucleotides. Then, the depth-first search algorithm is improved and used according to the design principle of pruning optimization to obtain the highly close melting temperature of the oligonucleotide set. In this way, uniformity of melting temperatures in oligonucleotide overlapped region is achieved. This will decrease the errors in gene assembly with PCR or LCR. Finally, the oligonucleotides that have homologous melting temperature needed for two-step assembly PCR-based synthesis of the target gene are deduced and outputted.